A novel homozygous splice‐site variant of NCAPD2 gene identified in two siblings with primary microcephaly: The second case report. Issue 1 (23rd May 2019) - Lin, Yunting; Zeng, Chunhua; Lu, Zhikun; Lin, Ruizhu; Liu, Li
Abstract: Here we describe the second case of primary microcephaly caused by a novel homozygous splice‐site variant at the NCAPD2 gene. The proband was born with microcephaly, and developed intellectual disability. Whole exome sequencing identified a canonical splice‐site variant, c.3477+2T>C, at the NCAPD2 gene. Sanger sequencing showed that the proband and her sibling, a symptomatic fetus, carried a homozygous c.3477+2T>C variant, while the unaffected parents were heterozygous and her younger brother had wild‐type alleles. To date, only one case of primary microcephaly with a homozygous splice‐site pathogenic variant at the NCAPD2 gene has been reported. Our study of two siblings provides additional evidence that NCAPD2 is a causative gene of primary microcephaly. This finding adds new knowledge in the etiology of microcephaly and contributes to more accurate counseling of affected families. Abstract :